Bilateral lateral patellar luxation in a calf. Issue 4 (3rd December 2019) - Strous, Emma; Willems, Nicole; Tobón Restrepo, Mauricio; Vos, Peter; Meij, Björn
Abstract : This case report documents the surgical treatment of bilateral lateral patellar luxation in a calf and the outcome by clinical examination, radiography, CT and postmortem examination. A 21‐day‐old calf was referred because of severe hindlimb weakness. Orthopaedic examination and radiographs revealed a grade 3 bilateral lateral patellar luxation with normal stifle bone anatomy. Surgery consisted of lateral desmotomy with excision of proliferative capsular tissues and imbrication of the medial retinaculum and resulted in anatomic repositioning of the patella. Aftercare consisted of treatment with ampicillin and meloxicam, a modified Robert Jones bandage with a spica splint and physiotherapy. In between surgeries CT was performed. The lameness in both hindlimbs gradually improved over time and the calf developed a normal stance and gait. After euthanasia CT was repeated and pathology performed, showing normal articular cartilage of the stifle and correct location of the patellae without signs of inflammation.